Development of machine- learning algorithms for 90- day and one- year mortality prediction in the elderly with femoral neck fractures based on the HEALTH and FAITH trials. (2023) - Dijkstra, H.; Oosterhoff, J. H. F.; Kuit, A. van de; IJpma, F. F. A.; Schwab, J. H.; Poolman, R. W.; Sprague, S.
No abstract available